Analysis of Acoustic Signals During the Optical Breakdown of Aqueous Solutions of Fe Nanoparticles - Baimler, Ilya V.; Lisitsyn, Andrey B.; Serov, Dmitriy A.; Astashev, Maxim E.; Gudkov, Sergey V. (Frontiers in Physics, 2020)
The study investigates the spectra of acoustic signals generating during the optical breakdown of colloidal solutions of iron nanoparticles. A characteristic form of the acoustic spectrum has been experimentally established, a distinctive feature of which is the presence of signals from an expanding and collapsing gas bubble. It is shown that the amplitude and area of these acoustic signals depend on the concentration of nanoparticles in the irradiated colloid. The effect of the concentration of nanoparticles on the bubble lifetime corresponding to the time interval between the acoustic spectrum signals corresponding to the birth and cavitation of a gas bubble has been studied.